(untitled) (Research, Society and Development, 2022)
Third molar extraction is one of the most routine procedures performed by dentists and often presents great postoperative discomfort. Platelet-rich fibrin is an alternative to minimize postoperative symptoms, exerting positive results in the healing process, in addition to being an attractive biomaterial to be used in clinical practice. With the present study, we seek to describe a clinical case report with the use of the L-PRF after extraction of the 3rd mandibular molar. We conclude that the use of L-PRF in third molar surgeries is an alternative capable of providing a less invasive postoperative period to the patient, which is within the reach of dentists, due to its low cost and ease of handling.